The Impact of Toxic Parenting on Children's Mental Health At High School - Ratih Susilawati; Naufal Ahmad Rijalul Alam (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
This This research is based on parenting patterns towards children. This parenting pattern consists of various habits of parents in nurturing, guiding, and leading children in a family environment. However, in contrast to these parenting patterns, in toxic parenting, parents tend to treat children badly. This study aims to analyze the impact of toxic parenting on the mental health of high school students. Toxic parenting has been shown to have a significant impact on children's mental health, including chronic stress, depression and anxiety. This study used a descriptive qualitative approach by conducting observations and in-depth interviews with five randomly selected high school students. The results of the analysis show that this parenting pattern inhibits children's emotional, social, and self-confidence development. Observations of the students' behavior also corroborated these findings, showing signs of emotional instability and limited social interaction. This study emphasizes the importance of effective family communication to minimize the negative impact of toxic parenting and establish a more emotionally and mentally healthy upbringing.